Money: their modes of signification and visualization in the new media situation - O. Y. Pavlova, (Ukrainian Cultural Studies, 2020)
The article is devoted to the study of the process of money circulation in the transformations of cultural practices. The role of money in the hierarchy of cultural practices in the emergence of new media, their status in the production of media products in general, and media images, in particular, is investigated. An analysis is made of the historical retrospective of the money genesis, as well as their particular historical forms of mate- rialization in the visual and semiotic aspects. It is argued that such a basic modern function of money as a measure of value and universal equiva- lent is not universal and timely. The de-differentiated form of cultural practice of gift-exchange, which precedes and inherits the calculative model of mind and world as an arithmetic problem, involves the representative role of money in the process of constructing an image. The specificity of incorporating money into the network of cultural practices and even certain types of social hierarchies determines their kind of materialization, referencing and visualization. The methodology of cultural research is aimed at revealing patterns of correlation of material, semiotic and visual dimensions of money circulation.So far the world was turning itself into "an arithmetic problem", the abstraction of quantitative measurement of money serves as the basis for the dominance of instrumental rationality, where the restoration of the magic of gifted money required additional effort to put through.With the transformation of media production strategies (the emergence of new media, the cheapening of micro-financing, the mass production, the metamorphosis of the status and image of the manufacturer), the semiotics of money is changing. The meaning of money in the hierarchy of socio-cultural practices in the process of digitization of cultural products does not disappear, but decreases.In the situation of new media, the calculation of money becomes again an internal moment of gift-exchange of the images measured by the sight (viewing, likes and reposts). This tendency has not become definitively dominant, but indicators of its realization are already obvious. The corresponding signification mod of symbolism (S. Lash's term) is forming. That is, the de-differentiation of the signified, the signifier and the refer- ent of money are included in the production of media-images, which represent a new form of ordering of cultural practices.
Keywords: money, signification, visualization, new media, cultural practice, cultural research